2022
DOI: 10.1038/s41419-022-05472-7
|View full text |Cite
|
Sign up to set email alerts
|

Laminins in tumor-derived exosomes upregulated by ETS1 reprogram omental macrophages to promote omental metastasis of ovarian cancer

Abstract: Tumor-derived exosomes participate in omental metastatic colonization of ovarian cancer by inducing an adaptive response in the tumor microenvironment. However, cell–cell communication via exosomes between primary tumor cells and the microenvironment of distant omentum and the mechanism of pre-metastatic niche formation are poorly understood. Here, we demonstrated that ETS1-overexpressing ovarian cancer cells secreted larger exosomes with higher laminin levels. In addition, ovarian cancer exosomes could be tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Flow cytometric analyses were performed using a DxFLEX flow cytometer (Beckman) as described previously [ 22 ]. For intracellular cytokine staining (ICS), the cells were first stimulated with 50 ng/ml PMA plus 750 ng/ml ionomycin for 6 h in the presence of 10 μg/ml protein transport inhibitor monensin (eBioscience).…”
Section: Methodsmentioning
confidence: 99%
“…Flow cytometric analyses were performed using a DxFLEX flow cytometer (Beckman) as described previously [ 22 ]. For intracellular cytokine staining (ICS), the cells were first stimulated with 50 ng/ml PMA plus 750 ng/ml ionomycin for 6 h in the presence of 10 μg/ml protein transport inhibitor monensin (eBioscience).…”
Section: Methodsmentioning
confidence: 99%
“…sEVs are important players in intercellular communication and are implicated in tumorigenesis and metastasis [ 8 11 , 13 , 14 , 16 ]. On the other hand, lactadherin overexpression has been associated with poor prognosis in several types of cancers, including BC [ 60 62 ]⁠.…”
Section: Resultsmentioning
confidence: 99%
“…This complex cellular interplay can be carried out through direct contact or mediated by extracellular signals (autocrine, paracrine, juxtracrine or endocrine) [ 7 ]⁠. Recent studies have shown that, especially in metastatic stages, the main route of extracellular communication is mediated by small extracellular vesicles (sEVs; mainly exosomes and microvesicles), which have been proposed to play essential roles in the promotion of tumorigenic capacities and the preparation of metastatic niches [ 8 11 ]⁠. sEVs are membrane-derived EVs that are released by various cell types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and cytosolic enzymes involved in Acetyl-CoA production (ACLY, ACSS2), carbohydrate (GPI, PYGB), lipid (FASN, OLAH), purine (ADSL, PNP) and folate (MTFHD1) metabolism (Supplementary figure 1B); (ii) Enhanced mucosal epithelium development: upregulation of serine-threonine kinase STK26 mediated apical membrane remodeling, 47 , RAB11b mediated microvilli formation and intestinal cell polarity 48 and ARHGDIB, CFL1, EPS8L2, FSCN1, PLS1, PIP, POTEJ, TWF2 that play roles in cell growth and development (Supplementary figure 1C); (iii) Proinflammatory response mitigation: upregulation of TPT1 mediated T and NK cell suppression 49 and USP14 stabilizing IDO1 immunosuppressive molecule,50 and downregulation of SNAP23 regulated cytokine release, 51 CD81 mediated Th2 polarization52 and MATN2/3 extracellular matrix proteins involved in proinflammatory responses53,54 (Supplementary figure1D); (iv) Lowered systemic bioavailability: downregulation of surface adhesion molecules ITGB1/4 and LAMB1 may reduce HMEV migration and translocation through integrin-laminin interaction[55][56][57] (Supplementary figure1E).…”
mentioning
confidence: 99%